Kingianic acids A–G, endiandric acid analogues from endiandra kingiana. - Leong, K.H. (Springer Verlag (Germany), 2014)
A phytochemical investigation of the methanolic extract of the bark of Endiandra kingiana led to the isolation of seven new tetracyclic endiandric acid analogues, kingianic acids A–G (1–7), together with endiandric acid M (8), tsangibeilin B (9) and endiandric acid (10). Their structures were determined by 1D- and 2D-NMR analysis in combination with HRMS experiments. The structure of compounds 9 and 10 were confirmed by single-crystal X-ray diffraction analysis. These compounds were screened for Bcl-xL and Mcl-1 binding affinities and cytotoxic activity on various cancer cell lines. Compound 5 showed moderate cytotoxic activity against human colorectal adeno-carcinoma (HT-29) and lung adenocarcinoma epithelial (A549) cell lines, with IC50 values in the range 15–17 µM, and compounds 3, 6 and 9 exhibited weak binding affinity for the anti-apoptotic protein Mcl-1.